Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer